An Investigation of the Measurement Estimation Strategies Used by Gifted Students - Erdogan, Fatma; Erben, Tuba (My University, 2020)
This study aimed to investigate the measurement estimation strategiesused by gifted students. Case study was used. 17 seventh gradestudents who were studying in the Science and Art Center located in aprovince in Eastern Anatolia Region of Turkey and who were identifiedas gifted participated in this study. The data was obtained through“The Measurement Estimation Skill Form” which includes nine openended tasks. In addition, clinical interviews were conducted with fivestudents. The data were analyzed using descriptive analysis. Thefindings of this study indicates that students use eight differentstrategies, which rough guess ,breaking down, using prior knowledge,reference point, unit iteration, comparison with referents, subdivisionclues and squeezing, in cases requiring measurement estimation. It wasalso found that while gifted students mostly used strategy “roughguess”, strategies “subdivision clues” and “squeezing” are used verylittle. Furthermore, the findings of this study show that gifted studentsdid not use different strategies at the expected level in themeasurement estimation situations.
Keywords: Eğitim; Eğitim Araştırmaları; Matematik